Lykken i tilbagetrækningen - Andersen, Michael Høxbro (K&K - Kultur og Klasse, 2016)
The concept of happiness becomes of great political importance in France during the Great Revolution. But 19th century French literature will question the possibility of producing a truly modern happiness through society. Withdrawing from post-revolutionary society then becomes a topos of the novel. As I argue in my paper, this is the case in the novels of Stendhal in particular. Inspired by Jean-Jacques Rousseau’s modern concept of otium, Stendhal articulates an opposition between an attitude that is strategic and histrionic, and a withdrawal into contemplation, with only the latter procuring any happiness: a happiness of sensation.